CLINICAL ENDOCANNABINOID DEFICIENCY (CED): A THEORETICAL FRAMEWORK AND THE THERAPEUTIC POTENTIAL OF MEDICAL CANNABIS IN NEUROIMMUNE AND PSYCHIATRIC DISORDERS (International Seven Journal of Multidisciplinary, 2025)
The Clinical Endocannabinoid Deficiency (CED) hypothesis suggests that insufficient production or signaling of endocannabinoids may be associated with chronic disorders such as migraine, fibromyalgia, irritable bowel syndrome, anxiety disorders, autoimmune diseases, among others. It highlights the need to understand the role of the endocannabinoid system (ECS) as a neuroimmune regulatory axis, in response to the increasing prevalence of multifactorial diseases that are difficult to manage clinically. This research aimed to review and analyze scientific evidence published between 2009 and 2022 regarding CED and the therapeutic use of medical cannabis, particularly cannabidiol (CBD) and tetrahydrocannabinol (THC), in ECS modulation. The adopted methodology was an integrative literature review based on PRISMA guidelines, using databases such as PubMed, Scopus, Web of Science, and Google Scholar. The results demonstrated correlations between ECS dysfunction and various clinical conditions with poor response to conventional treatments. Clinical studies reported significant symptom improvement with CBD-rich extracts, and genetic data and inflammatory markers reinforced the biological plausibility of CED. It is concluded that CED is a viable explanatory model for multiple chronic disorders. When administered through individualized protocols, medical cannabis represents a promising therapeutic alternative. The incorporation of ECS knowledge into clinical practice may foster precision medicine in neuropsychiatry and immunology.